Assembly line performance and modeling - Arun B. Rane; Vivek K. Sunnapwar (Journal of Industrial Engineering International, 2017)
Automobile sector forms the backbone of manufacturing sector. Vehicle assembly line is important section in automobile plant where repetitive tasks are performed one after another at different workstations. In this thesis, a methodology is proposed to reduce cycle time and time loss due to important factors like equipment failure, shortage of inventory, absenteeism, set-up, material handling, rejection and fatigue to improve output within given cost constraints. Various relationships between these factors, corresponding cost and output are established by scientific approach. This methodology is validated in three different vehicle assembly plants. Proposed methodology may help practitioners to optimize the assembly line using lean techniques.
Keywords: 650; Simulation; Optimization; Lean; Mathematical modeling; Line balancing; Output; Utilization; Efficiency; Cost constraint; Downtime